Respon pertumbuhan dan hasil tanaman terung (solanum melongena l.) terhadap pemberian pupuk organik cair ekstrak buah mengkudu (morinda citrifolia l.) di lahan rawa lebak - Meci Yuniastuti Rahma; Nurrohmah Nurrohmah; Nur Hasanah (Jurnal Agrotek Ummat, 2023)
This study aims to determine the growth response of eggplant (Solanum melongena L.) to liquid organic fertilizer noni fruit (Morinda citrifolia L.) grown in lebak swamps. In this study, a randomized block design (RBD) method was used which consisted of 6 treatments and 4 replications. The concentration of noni fruit extract used was P0 = 0 ml, P1 = 6 ml, P2 = 8 ml, P3 = 10 ml, P4 = 12 ml, P5 = 14 ml. Observations were made on plant height, number of branches, flowering time, fruit number and fruit length. The results of the analysis of variance showed that the response of plants to the influence of noni fruit liquid fertilizer was very good for the age of flowering, number of fruits, fruit length. From the results of the study it can be concluded that the administration of noni fruit liquid organic fertilizer has a very significant effect on the age of flowering and the number of fruits and has a significant effect on the length of eggplant fruit. In the P5 treatment with a concentration of 14 ml gave the best effect, it can be used as an effective dose for growing eggplant plants.